In situ and ex situ bioremediation of heavy metals: the present scenario - Paul, Oindrila; Jasu, Amrita; Lahiri, Dibyajit; Nag, Moupriya; Ray, Rina Rani (Journal of Environmental Engineering and Landscape Management, 2021)
Enhanced population growth, rapid industrialization, urbanization and hazardous industrial practices have resulted in the development of environmental pollution in the past few decades. Heavy metals are one of those pollutants that are related to environmental and public health concerns based on their toxicity. Effective bioremediation may be accomplished through “ex situ” and “in situ” processes, based on the type and concentration of pollutants, characteristics of the site but is not limited to cost. The recent developments in artificial neural network and microbial gene editing help to improve “in situ” bioremediation of heavy metals from the polluted sites. Multi-omics approaches are adopted for the effective removal of heavy metals by various indigenous microbes. This overview introspects two major bioremediation techniques, their principles, limitations and advantages, and the new aspects of nanobiotechnology, computational biology and DNA technology to improve the scenario.